2017
DOI: 10.1177/0333102416686302
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders: Old ideas and new concepts

Abstract: Background Temporomandibular disorders (TMD) is an umbrella term for pain and dysfunction involving the masticatory muscles and the temporomandibular joints (TMJs). TMD is the most common orofacial pain condition. Its prominent features include regional pain in the face and preauricular area, limitations in jaw movement, and noise from the TMJs during jaw movements. TMD affects up to 15% of adults and 7% of adolescents. Chronic pain is the overwhelming reason that patients with TMD seek treatment. TMD can asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
324
1
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(357 citation statements)
references
References 67 publications
8
324
1
24
Order By: Relevance
“…Occlusal appliances were the most frequent treatment performed, in line with our previous report , but other treatments, such as information and jaw exercises, remained scarce despite the reported benefits of these approaches for this patient group . Instead, information and jaw exercises were primarily represented in the group ‘treatment not charged for’.…”
Section: Discussionsupporting
confidence: 81%
“…Occlusal appliances were the most frequent treatment performed, in line with our previous report , but other treatments, such as information and jaw exercises, remained scarce despite the reported benefits of these approaches for this patient group . Instead, information and jaw exercises were primarily represented in the group ‘treatment not charged for’.…”
Section: Discussionsupporting
confidence: 81%
“…21 Oromandibular treatment with occlusal splints is often recommended but has not yet been tested in trials of reasonable quality and cannot be recommended in general. 22,23 There are also conflicting results regarding the efficacy of acupuncture for the treatment of TTH. 19 Psychological treatment strategies have achieved reasonable scientific support for effectiveness.…”
Section: Treatment Is Non-pharmacological Treatment Relevant For Tth-mentioning
confidence: 99%
“…I would also like to highlight a small study which found C1 root simulation referred pain to the periorbital region in patients with a history of migraine. 1 I am not sure what to make of the authors' statement of an "economic burden" due to this clinical symptom. I can see where "unnecessary" diagnostic tests may be performed when a patient has neck related migraine.…”
Section: Kaniecki Rg Totten J Cervicalgia In Migrainementioning
confidence: 95%
“…RGK should have more to say on that, but I reference below his first report on cervicalgia in migraine. 1 Some of the data were later summarized: "A subset of 30 patients from a study of 144 patients diagnosed with IHS-defined migraine treated 278 headaches, 231 of which were accompanied by neck pain, with sumatriptan or a pharmacologically similar triptan. The percentage of mild, moderate, or severe headaches with a pain-free response 2 h after dosing was 68% for head pain and 73% for neck pain."…”
mentioning
confidence: 99%